The new 4‐m robotic telescope. Issue 1 (28th March 2019) - Gutiérrez, C. M.; Arnold, D.; Copley, D.; Copperwheat, C. M.; Harvey, E.; Jermak, H.; Knapen, J.; McGrath, A.; Oria, A.; Rebolo, R.; Steele, I. A.; Torres, M.
Abstract : We present a project to build a 4‐m‐diameter telescope (New Robotic Telescope [NRT]) with fully robotic operation. The telescope will be sited at the Observatory of Roque de los Muchachos in the island of La Palma (Spain). When it enters into operation in 5 years' time, it will be likely the largest robotic telescope in the world. This, in conjunction with the extremely fast response and the versatile and flexible instrumentation in the optical and near‐infrared ranges, will make the NRT a world‐leading facility in the area of time‐domain astrophysics. Here we discuss some of the main scientific cases, the mechanical and optical design, the control system, first light instrumentation, and the timeline of the project.